Teaching digital ethos: emphasizing the rhetorical impact of hypertextuality and intertextuality in the digital environment - DeCuir, Erin E., author; Gage, Scott, advisor; Souder, Donna, committee member; Checho, Colleen, committee member (Colorado State University. Libraries, 2014)
The need to adapt traditional techniques of rhetorical analysis to new and emergent forms of digital technology is one of the current challenges confronting rhetoric and composition pedagogy (Warnick, 2001; Hocks, 2003; Warnick, 2005; Fife, 2010). Digital ethos functions as an illustrative example of this challenge as composition courses attempt to address the ways credibility is constructed and maintained in web-based environments (Hocks, 2003; DigiRhet.org, 2006; Clark, 2010; Fife, 2010; Walker, et al., 2011; Gillam & Wooden, 2013). Current scholarship and textbooks indicate that the field continues to rely on traditional rhetorical analysis techniques to teach digital ethos, including an emphasis on ethos as the product of a single text with fixed boundaries (Enos & Borrowman, 2001; DigiRhet.org, 2006; Downs & Wardle, 2007; Clark, 2010; Fife, 2010). However, because the Internet is a hypertextual system of internetworked texts, it is necessary for FYC courses to teach a construction of ethos that considers texts as they are linked and circulated within the system. I argue in this thesis for a digital ethos heuristic that emphasizes (1) the relationships constructed through hypertextual links and (2) the ways in which those relationships create intertextual meaning that impacts and influences digital ethos construction. In this way, we can begin to adapt techniques of rhetorical analysis both to acknowledge and to critique the ways in which web-based technologies impact how we are to understand and teach composition in the current moment.
Keywords: composition; rhetoric; intertextuality; hypertextuality; digital ethos